Does the Reliability of Reporting in Injury Surveillance Studies Depend on Injury Definition?. Issue 3 (13th March 2018) - Cross, Matthew; Williams, Sean; Kemp, Simon P.T.; Fuller, Colin; Taylor, Aileen; Brooks, John; Trewartha, Grant; Stokes, Keith
Background: Choosing an appropriate definition for injury in injury surveillance studies is essential to ensure a balance among reporting reliability, providing an accurate representation of injury risk, and describing the nature of the clinical demand. Purpose: To provide guidance on the choice of injury definition for injury surveillance studies by comparing within- and between-team variability in injury incidence with >24-hour and >7-day time-loss injury definitions in a large multiteam injury surveillance study. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: Injury data were reported for 2248 professional rugby union players from 15 Premiership Rugby clubs over 12 seasons. Within-team percentage coefficient of variation and mean between-team standard deviation (expressed as a percentage coefficient of variation) in injury incidence rates (injuries per 1000 player match hours) were calculated. For both variables, a comparison was made between >24-hour and >7-day injury incidence rates in terms of the magnitude of the observed effects. Results: The overall mean incidence across the population with a >24-hour time-loss injury definition was approximately double the reported incidence with the >7-day definition. There was a 10% higher between-team variation in match injury incidence rates with the >24-hour time-loss definition versus the >7-day definition. Conclusion: There was a likely higher degree of between-team variation in match injury incidence rates with a >24-hour time-loss definition than with a >7-day definition of injury. However, in professional sports settings, it is likely that the benefits of using a more inclusive definition of injury (improved understanding of clinical demand and the appropriate and accurate reporting of injury risk) outweigh the small increase in variation in reporting consistency.